2022
DOI: 10.1186/s41100-022-00451-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the 6th Japanese wave of COVID-19 in hemodialysis patients

Abstract: Background We examined the clinical characteristics of hemodialysis patients with COVID-19 during the 6th wave of infection (mainly Omicron variant) in Japan. Methods Hemodialysis patients admitted in January 2022 and thereafter were grouped as the 6th wave group (n = 53), while others were grouped as the 1st–5th wave group (n = 47). Results The proportion of vaccinations was significantly higher in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The Omicron variant accounted for the majority of the 6th wave of COVID-19 cases in Japan. In this study, sore throat was more frequent in the 6th wave group (60.4%) than in the 1st–5th wave groups (10.6%; p < 0.0001) [ 9 ]. In our study, sore throat was the least common symptom (14%).…”
Section: Discussionmentioning
confidence: 96%
“…The Omicron variant accounted for the majority of the 6th wave of COVID-19 cases in Japan. In this study, sore throat was more frequent in the 6th wave group (60.4%) than in the 1st–5th wave groups (10.6%; p < 0.0001) [ 9 ]. In our study, sore throat was the least common symptom (14%).…”
Section: Discussionmentioning
confidence: 96%
“…However, most existing studies have focused on the immunogenicity of booster vaccination, and its real-world benefits on the clinical outcomes of COVID-19 have less been investigated in the HD population, particularly in those receiving oral antiviral agents. In addition, although the combination of SARS-CoV-2 vaccines and antiviral treatments is considered beneficial for patients with COVID-19 who are at high risk of disease progression, current reports have yielded mixed results on this issue, and the integrated effects of vaccination and oral antiviral agents have yet to be characterized in HD patients [ 34 , 35 , 49 , 50 ]. A previous study utilizing an agent-based mathematical model suggested that combining SARS-CoV-2 vaccines and antiviral treatments could synergistically reduce COVID-19-related hospitalization and mortality in the overall population [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study utilizing an agent-based mathematical model suggested that combining SARS-CoV-2 vaccines and antiviral treatments could synergistically reduce COVID-19-related hospitalization and mortality in the overall population [ 49 ]. Two observational studies in Poland and Japan suggested that combining booster vaccination and molnupiravir treatment was associated with a shorter illness duration and fewer medical requirements in HD patients with COVID-19, although the sample sizes were both small [ 34 , 35 ]. In contrast, another open-label trial addressing the effects of molnupiravir in a highly vaccinated population in the UK (3-dose vaccination, 94%) indicated that hospitalization and mortality might be primarily avoided via extensive vaccination rather than antiviral agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Twenty-five studies were from populations primarily of European ancestry [9,30,, seventeen studies on East Asians [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] (note that one of these studies, [75], reports on the same cohort as [74], and therefore was removed from the meta-analysis), eight studies on South Asians [79][80][81][82][83][84][85][86], four studies on Latinos/Hispanics [87][88][89][90], five studies on populations in Africa [91][92][93][94][95], and three studies from the Middle East [96][97][98]. The location of studies, with the prevalence indicated by the color intensity, and the cohort size indicated by the size of the circles, shows that Western countries report the highest prevalence, while studies from East Asia and the Middle East report the lowest prevalence (Fig.…”
Section: Properties Of Studiesmentioning
confidence: 99%